2007
DOI: 10.1111/j.1447-0349.2007.00474.x
|View full text |Cite
|
Sign up to set email alerts
|

How involuntary commitment impacts on the burden of care of the family

Abstract: Little research has examined how, or if, involuntary commitment has impacted on the burden experienced by the family. This paper reports a qualitative study which explored how involuntary commitment under the Mental Health Act (MHA) 2000 in Queensland, Australia impacted on families of people with mental illness. Family members of a person with a mental illness, under involuntary commitment at the time or in the previous 12 months, participated in focus groups. Thematic analysis was used to determine the theme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 37 publications
1
33
0
Order By: Relevance
“…They need to feel that their experience is acknowledged and worked on. Hallam (2007) found that treatment cultures which exclude relatives, can lead to a climate of cooperation that alienates the family from the patient's life. Such a development could make relatives distance themselves from the patient to protect themselves rather than involving themselves to promote the patient's recovery process.…”
Section: Discussionmentioning
confidence: 99%
“…They need to feel that their experience is acknowledged and worked on. Hallam (2007) found that treatment cultures which exclude relatives, can lead to a climate of cooperation that alienates the family from the patient's life. Such a development could make relatives distance themselves from the patient to protect themselves rather than involving themselves to promote the patient's recovery process.…”
Section: Discussionmentioning
confidence: 99%
“…1996) makes it imperative to include resilience in the conception of the experience of informal caregivers. Informal caregivers feel relief if the responsibility for the welfare of the older person with a mental illness can be shared not only with other family members or friends but also with a mental health professional who is familiar with the situation (Hallam 2007).…”
mentioning
confidence: 99%
“…Diverse activities. Informal caregivers who maintain some form of employment express less distress because work provides a distraction from the impact of the illness (Hallam 2007). Relatives who are forced to give up leisure activities or their occupation have fewer sources of positive feedback.…”
mentioning
confidence: 99%
“…There is international interest in, and continued concern about, the potential long-term impact of involuntary admission to psychiatric institutions, and the effect this coercive action has on a person's well-being and human rights (van den Hooff et al 2015;Hughes et al 2009;Johansson & Lundman 2002;McGuinness et al 2013;Newton-Homes & Mullen 2011;Svindseth et al 2007). In Ireland, the Mental Health Act (MHA) 2001 was implemented on 1 November 2006, replacing previous legislation, the Mental Treatment Act (MTA) 1945, and incorporating a number of changes to the process of involuntary admission and treatment of service users.…”
Section: Introductionmentioning
confidence: 99%
“…Other stakeholders, including GP, relatives, and MHN, report that the application process of involuntary detention is time-consuming and complex, and impacts negatively on long-term relationships with individuals. These stakeholders also report often feeling alone when dealing with the crisis (Doherty et al 2014;van den Hooff & Goossensen 2015;Jabbar et al 2010;Jankovic et al 2011;Jespen et al 2010;Røtvold & Wynn 2014). Studies exploring GP perspectives highlight the complexity of the admission process and associated stresses.…”
Section: Introductionmentioning
confidence: 99%